Steamboats and smaller vessels on the Snake River with building construction on the right at Nome, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. On verso of image: Snake River, Nome, Alaska Warner 142 Filed in Alaska series.